Glycan-Lectin interactions between platelets and tumor cells drive hematogenous metastasis - Longqiang Shu; Shanyi Lin; Shumin Zhou; Ting Yuan (Platelets, 2024)
Glycosylation is a ubiquitous cellular or microenvironment-specific post-translational modification that occurs on the surface of normal cells and tumor cells. Tumor cell-associated glycosylation is involved in hematogenous metastasis. A wide variety of tumors undergo aberrant glycosylation to interact with platelets. As platelets have many opportunities to engage circulating tumor cells, they represent an important avenue into understanding the role glycosylation plays in tumor metastasis. Platelet involvement in tumor metastasis is evidenced by observations that platelets protect tumor cells from damaging shear forces and immune system attack, aid metastasis through the endothelium at specific sites, and facilitate tumor survival and colonization. During platelet-tumor-cell interactions, many opportunities for glycan-ligand binding emerge. This review integrates the latest information about glycans, their ligands, and how they mediate platelet-tumor interactions. We also discuss adaptive changes that tumors undergo upon glycan-lectin binding and the impact glycans have on targeted therapeutic strategies for treating tumors in clinical settings.